2015
DOI: 10.1038/srep16671
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of medical taping concept in primary dysmenorrhoea: a two-armed randomized trial

Abstract: In 2014, we assessed the effectiveness of Medical Taping Concept (MTC) in Primary Dysmenorrhoea (PD) with a single-blind, two-armed clinical trial (NCT02114723, ClinicalTrials.gov) with a follow-up of 4 menstrual cycles (pre-intervention: 2 months; post-intervention: 2 months) in a sample formed by 129 Spanish women aged 18–30 years with PD. We had two groups: intervention group (75), MTC covering T-11 and T-12 dermatomes; control group (54), another taping in both greater trochanter areas. Our main outcome me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
23
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(25 citation statements)
references
References 25 publications
(25 reference statements)
2
23
0
Order By: Relevance
“…In the last decade, several authors have noted the need to further study both the pharmacological and non-pharmacological management of menstrual pain [ 10 , 11 , 35 ], especially considering that 18% of non-steroidal anti-inflammatory treatments are ineffective for dysmenorrhea, the primary treatment for this condition [ 36 ]. There is increasing evidence of the efficacy of non-pharmacological methods for dysmenorrhea, such as aerobic exercise, yoga, taping and transcutaneous electrical nerve stimulation [ 20 , 21 , 37 , 38 , 39 ]. Furthermore, a study conducted in the USA among women suffering from dysmenorrhea identified the reasons why women did not seek medical advice: they believed professionals would be unable to help, they distrusted the available treatments and felt ashamed or fearful of seeking help for this problem [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…In the last decade, several authors have noted the need to further study both the pharmacological and non-pharmacological management of menstrual pain [ 10 , 11 , 35 ], especially considering that 18% of non-steroidal anti-inflammatory treatments are ineffective for dysmenorrhea, the primary treatment for this condition [ 36 ]. There is increasing evidence of the efficacy of non-pharmacological methods for dysmenorrhea, such as aerobic exercise, yoga, taping and transcutaneous electrical nerve stimulation [ 20 , 21 , 37 , 38 , 39 ]. Furthermore, a study conducted in the USA among women suffering from dysmenorrhea identified the reasons why women did not seek medical advice: they believed professionals would be unable to help, they distrusted the available treatments and felt ashamed or fearful of seeking help for this problem [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…There are several treatments to relieve primary dysmenorrhea such as consumption of non-steroidal antiinflammatory drugs (NSAIDs) and oral contraceptives (11). The low level of female satisfaction is reported for NSAIDs due to a failure rate of 20-25% and non-tolerable side effects (12) addition to increase in cardiovascular disease risks (13).…”
Section: Introductionmentioning
confidence: 99%
“…There are several treatments for PD like non-steroidal anti-inflammatory drugs (NSAIDs), oral contraceptive drugs, physical therapy interventions, Chinese traditional herbology, and so on. 5 Among them, NSAIDs are the first-line treatment. 6 There are many types of NSAIDs which are widely used as analgesics and anti-inflammatory agent through inhibiting cyclooxygenase (COX) enzymes including COX-1 and COX-2.…”
Section: Introductionmentioning
confidence: 99%